(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess patient satisfaction at the Outpatient Department of Transport Hospital in 2025 and analyze associated factors. Methods: A cross-sectional study was conducted among all patients visiting the outpatient department in 2025. Data were collected using a structured questionnaire covering demographics, waiting time, medical costs, and satisfaction across multiple domains (physicians, nurses, support staff, facilities, service outcomes). Descriptive statistics and regression analysis were applied to determine related factors. Results: Most patients reported high satisfaction, particularly regarding physicians’ professionalism and nurses’ care. However, waiting time and hospital facilities were less positively rated. Regression analysis indicated that waiting time, income, and education level significantly influenced satisfaction (p < 0.05). Conclusion: Patients were generally satisfied with healthcare services, but improvements in infrastructure and waiting time reduction are needed. Findings provide evidence to guide hospital quality improvement strategies.